2010
DOI: 10.1111/j.1442-2042.2010.02475.x
|View full text |Cite
|
Sign up to set email alerts
|

Modified Koyanagi's procedure for proximal hypospadias: Our experience

Abstract: Koyanagi described an elegant technique for one-stage proximal hypospadias repair. It is particularly suited for the most severe forms of hypospadias. A modified Koyanagi technique was used to repair the hypospadias in 14 children, aged 3-9 years. One child developed breakdown of the suture line, three other children developed small urethrocutaneous fistula needing closure and one child had post-operative meatal stenosis. Despite the high rate of complications, modified Koyanagi's procedure is a good procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Complications, what so ever the technique used, were high and troublesome [ 6 ]. Because koyanagi technique used a parameatal vascularized flaps [ 7 ], it was first described as the technique to treat most sever, even perineal, hypospadias –contrary to duckett repair-with or without peno-scrotal transposition, in one stage [ 8 ]. Moreover, this technique lacked the circular anastomosis at the base of the urethroplasty which theoretically decreased the stenosis rate [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complications, what so ever the technique used, were high and troublesome [ 6 ]. Because koyanagi technique used a parameatal vascularized flaps [ 7 ], it was first described as the technique to treat most sever, even perineal, hypospadias –contrary to duckett repair-with or without peno-scrotal transposition, in one stage [ 8 ]. Moreover, this technique lacked the circular anastomosis at the base of the urethroplasty which theoretically decreased the stenosis rate [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this technique lacked the circular anastomosis at the base of the urethroplasty which theoretically decreased the stenosis rate [ 8 , 9 ]. In addition, using the koyanagi repair [7] , no bulking and no apparent penile torsion were noted [ 10 ]. Moreover, following this technique, there was always enough para -meatal tissues for the urethroplasty [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…They reported complications of meatal stenosis (16%), urethral-cutaneous fistula (39%), meatal recession (19%), and diverticulum (9%). Nerli et al (18) published their study in 2010, they worked on sample sized 14 patients, their age ranged from 3 to 9 years old. 28% of the patients had associated external genitalia anomaly.…”
Section: Discussionmentioning
confidence: 99%
“…Hayashi et al [32] reported on 12 children treated with a modified neo-Koyanagi repair, with only one complication, a fistula. Nerli et al [33] reported on 14 children who had a repair using the modified Koyanagi method, with five complications, i.e. one dehiscence, three with fistula and one meatal stenosis.…”
Section: Discussionmentioning
confidence: 99%